The Effects of Protective Footwear on Spine Control and Lifting Mechanics - Mavor, Matthew (Université d'Ottawa / University of Ottawa, 2018)
Low back pain (LBP) is a common condition that affects all age groups and sexes. Although the development of LBP is multifactorial, the performance of lifting-based manual material handling (MMH) tasks are recognized as a primary risk factor. Many occupations that involve MMH tasks are performed in hazardous environments, where personal protective equipment (PPE) must be worn. Among the most commonly prescribed forms of PPE in Canada are CSA Grade 1 steel-toed work boots. According to the hazards present on the jobsite, workers may need to wear steel-toed work boots with/without a metatarsal guard or be able to wear steel-toed shoes (no upper). However, the amount of research on the interaction between protective footwear and human motion is limited. Therefore, the purpose of this thesis was to assess the effects of steel-toed shoes (unlaced), steel-toed boots (work boot), and steel-toed boots with a metatarsal guard (MET) on lifting mechanics. Specifically, three-dimensional kinematics of the lower limbs and trunk, sagittal net reaction moments of the low back, and local dynamic stability (LDS) of the lower limbs, lower back, and upper back were analyzed. Twelve males and 12 females were recruited to participate in this research project. Participants performed a repetitive lifting task at 10% of their maximum back strength, under three block-randomized footwear conditions. Ankle dorsiflexion was negatively affected by footwear type, where dorsiflexion was reduced the most in the MET condition compared to the unlaced condition (p < 0.01). However, there were no other main effects of footwear type on any other variable tested, and both male and female participants were able to maintain similar lifting mechanics and LDS values when moving up the kinematic chain. It is possible that participants were able to preserve their kinematics and stability through the appropriate recruitment of muscles, which may have implications for an increase in compressive and shear force on the spine and should be explored further in the future.
Keywords: Ergonomics; Spine; Musculoskeletal Modeling; Biomechancis